DevOps practices in incident management process - Faustino, João Pedro Carvalho (2019)
This research aims to investigate how DevOps culture can be applied in the incident management process to improve it. Given the exploratory approach of the research, it was performed a case study. For this case study an application management team was studied where a sample of 10 persons were interviewed. This team solves incidents and provides the necessary support to the users in their daily business tasks using DevOps practices. During this case study three data collection methods were used: semi structured interviews, document analysis and observation. This research provides novel findings about a possible relation between DevOps practices and incident management phases as well as on “why” and “how” can these practices help incident management. The results are supported by metrics, like time between releases, total of over delivered incidents solutions and releases per month, to justify how this team’s performance have increased after the implementation of DevOps practices. The novelty of the findings brings advantages for academics, and due to the exploratory nature of this research, it extends the body of knowledge. It also provides contributions for practitioners, by showing how these practices can be applied and the result of the implementation of these practices. Directions of future work are also presented.